Immunomodulation as the main characteristic of vegetable oils: a review - D.P. Tres; S.T. Nicolau; T.S. Ayala; R.A. Menolli (Grasas y Aceites)
Known for being a functional food, vegetable oil is widely used because of its nutraceutical activity. It notable that one third of all traditional medicines are intended to treat inflammatory disorders. Vegetable oils are basically composed of linoleic and alpha-linolenic acids, which are polyunsaturated fatty acids (PUFA) classified as essential, and monounsaturated fatty acids (MUFA) such as oleic acid, are classified as non-essential. Olive, sunflower, flaxseed, and chia oil are rich in these fatty acids, and their benefits are directly linked to these fatty acid contents. The benefits in their consumption by the population worldwide is proven, mainly promoting the balance of the lipid profile, cardiovascular aspects, decrease in blood pressure, and healing effects when used topically. Most of these benefits come from the immunomodulatory effects of vegetable oils, mainly the anti-inflammatory activities triggered by the unsaturated fatty acids present in these oils.